Reconstruction of the Formulation of Rehabilitation Sanctions for Narcotics Abusers from the Perspective of Criminal Law Policy - Sutan Siregar; Muksana Pasaribu; Putoro Dongoran (CV. RADJA PUBLIKA, 2026)
Indonesia's narcotics criminal law policy continues to reflect normative tensions between a repressive criminalization approach and a rehabilitative paradigm. Although the law recognizes narcotics abusers as individuals requiring recovery, law enforcement practices remain predominantly imprisonment-oriented because rehabilitation is positioned as an alternative rather than a primary sanction. This study aims to examine: (1) the weaknesses in the formulation of rehabilitation sanctions within Indonesian criminal law policy, and (2) the normative reconstruction model capable of positioning rehabilitation as the primary response to narcotics abusers. This research employs normative legal research using statutory, conceptual, case, and comparative approaches. The data sources consist of primary legal materials, including the Narcotics Law and the Criminal Code, supported by secondary and tertiary legal materials analyzed qualitatively through legal interpretation and juridical reasoning. The findings reveal that the principal weakness lies in the formulation of Articles 103 and 127 of the Narcotics Law, as well as the absence of explicit rehabilitation provisions in the new Criminal Code, resulting in legal ambiguity and disparities in judicial decisions. Consequently, correctional institutions experience severe overcrowding, with more than 40 percent of inmates being narcotics offenders, while prisons increasingly function as spaces for the reproduction of crime rather than rehabilitation. This study recommends reconstructing the sanction formulation through revision of Article 609 of the Criminal Code to clearly distinguish narcotics abuse from illicit trafficking, alongside transforming the integrated assessment mechanism from discretionary authority into an imperative normative obligation. The originality of this research lies in shifting the analytical focus from implementation issues to the formulation of criminal law policy and developing a normative reconstruction model integrating therapeutic jurisprudence and restorative justice within the national criminal justice system.